Permeable concrete: Current state-of-the-art and perspectives - Khong, Sheh Ching; Yee, Jia Jun; Tee, Kong Fah; Chin, Siew Choo (Springer, 2024)
This paper examines permeable concrete, referred to as pervious concrete, which is characterized by having minimal to no fine aggregates in its composition. This unique type of concrete allows water to pass through due to the voids within its internal structure. The lack of fine aggregates means that the strength of permeable concrete depends on the coarse aggregate and its bond with the cement paste, resulting in lower strength properties that limit its practical applications. Nevertheless, using permeable concrete in contemporary infrastructure is crucial for building climate-resilient cities and aligning with the United Nations Sustainable Development Goals, specifically Goal 11: Sustainable Cities and Communities. Consequently, concrete researchers have started exploring innovative approaches to enhance the properties of permeable concrete. This study reviews the solutions proposed by researchers, which include improvements to the basic permeable concrete mix design, the use of supplementary cementitious materials, the replacement of coarse aggregates in the mix, and the incorporation of steel and fiber reinforcements. The latest advancements from previous studies are presented and discussed, along with a summary of potential future research directions in the field of permeable concrete.